Determining factors in relation to lymphovascular characteristics and anastomotic configuration in supermicrosurgical lymphaticovenous anastomosis – A retrospective cohort study. (September 2020) - Tsai, Po-Lun; Wu, Shao-Chun; Lin, Wei-Che; Mito, Daisuke; Chiang, Min-Hsien; Hsieh, Ching-Hua; Yang, Johnson Chia-Shen
Abstract: Introduction: Supermicrosurgical lymphaticovenous anastomosis (LVA) can be performed in different configuration such as end-to-end (LVEEA), end-to-side (LVESA), and side-to-end (LVSEA). Each configuration has its own advantages and disadvantages. However, it has remained ambiguous as to which anastomotic o configuration to choose. The aim of this study is to analyze and compare the relative sizes of lymphatic vessel (LV) and recipient vein (RV), in attempts to provide the basis for proper selections of the anastomotic configuration. Methods: From March 2016 to October 2018, 100 lymphedema patients with 103 lymphedematous lower limbs (stage I-III) were included. All patients underwent supermicrosurgical LVA. Demographic data and intraoperative findings, including the number and size of the LV/RV, the size discrepancies, and the numbers of LVA performed were recorded. The severity of LVs were classified based on the lymphosclerosis classification (s0, s1, s2, and s3). One-way ANOVA test and post hoc analysis with Bonferroni's correction were performed for size discrepancy analysis. Results: A total 730 LVA were performed with 621 LVs and 468 RVs, averaging 7.1 LVA per limb. Of these, 367 (50.3%) were LVEEA, 333 (45.6%) were LVESA, and 30 (4.1%) were LVSEA. The average LV and RV size was 0.61 ± 0.35 mm and 0.87 ± 0.43 mm, respectively ( p < 0.001). The average LV size in different configuration: LVEEA = LVESA < LVSEA ( p < 0.001); The average RV size: LVEEA = LVSEA < LVESA ( p < 0.001); The size discrepancy: LVESA > LVSEA > LVEEA ( p < 0.001).The LVSEA group has more s1 lymphatic vessels as opposed to LVEEA and LVESA ( p = 0.004). Conclusion: The size and the comparative discrepancy between the LVs and RVs are the determining factors for proper anastomotic configuration selection during LVA. LVESA was more frequently performed when vessel size discrepancy was larger. The efficacy of each anastomotic configuration has yet to be determined. Highlights: The determining factors of anastomotic orientation, such as lymphaticovenous end-to-end (LVEEA), end-to-side (LVESA), and side-to-end (LVSEA), are the sizes of the lymphatic vessel (LV) and recipient vein (RV), and the relative distance between them. 730 LVA were performed with 621 LVs and 468 RVs. 50.3% were LVEEA, 45.6% were LVESA, and 4.1% were LVSEA. The average LV and RV size was 0.61 ± 0.35 mm and 0.87 ± 0.43 mm (p < 0.001). The size discrepancy was LVESA > LVSEA > LVEEA (p < 0.001).